An improved Mesh Adaption and Refinement approach to Cavitation Simulation (MARCS) of propellers. (1st January 2019) - Yilmaz, Naz; Atlar, Mehmet; Khorasanchi, Mahdi
Abstract: This paper presents the improvements of cavitation modelling for marine propellers particularly developing tip vortex cavitation. The main purpose of the study is to devise a new approach for modelling tip vortex cavitation using Computational Fluid Dynamics (CFD) methods with commercial software, STAR-CCM+. The INSEAN E779A model propeller was used for this study as a benchmark propeller. Utilizing this propeller, firstly, validation studies were conducted in non-cavitating conditions together with grid and time step uncertainty studies. Then, the cavitation was simulated on the propeller using a numerical cavitation model, which is known as the Schnerr–Sauer model, based on the Rayleigh-Plesset equation. While a Reynolds Averaged Navier Stokes (RANS) model was used for open water simulations, Detached Eddy Simulations (DES) and Large Eddy Simulations (LES) models were preferred for cavitation simulations to capture the cavitation and evaluate its effect on propeller performance accurately. Although the comparison with the benchmark experimental data showed good agreement for the thrust and torque coefficients as well as sheet cavitation pattern, tip vortex cavitation could not be adequately simulated using the existing method. After an evaluation of the interaction between cavitation modelling and generated meshes, two techniques, which involved volumetric control and adaptive mesh refinement, were used in combination on the region where the tip vortex cavitation is likely to occur. The first technique, which is called a 'volumetric control method', was developed using spiral geometry around the propeller tip region to generate a finer mesh for capturing tip vortex cavitation. Although this method gave better tip vortex cavitation extension than the method without any mesh refinement or with tube refinement, it still required to be improved to extend the tip vortices further into the propeller slipstream. The second method, which is called 'adaptive mesh refinement', was introduced using the pressure distribution data from the results of the 'volumetric control method'. This improved approach, which is called "Mesh Adaption and Refinement for Cavitation Simulation (MARCS)", has been successfully applied to simulate the tip vortices trailing from the blades of the INSEAN E779A propeller as demonstrated in the paper. The results of the simulations showed an excellent agreement with the experiments in the open literature by tracking the tip vortex cavitation along this propeller's slipstream. Highlights: CFD calculations for a propeller in uniform flow, non-cavitating and cavitating conditions. Verification and validations (grid and time-step independency) in non-cavitating conditions. Propeller cavitation simulations including particularly tip vortex cavitation. Development of an adaptive and phenomenological mesh refinement approach for simulating tip vortex cavitation (MARCS).